PENERAPAN STRATEGI PEMBELAJARAN IPS BERBASIS KEARIFAN LOKAL DALAM MEMBANGUN KARAKTER SISWA SEKOLAH DASAR - Firmaning Lestari, Maghfirotul; Fina Rohmatul Ummah; Nurul Hidayatus Sholihah; Fathur Rahman Arrozi; Mu’allimin (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Abstract This study aims to explore local wisdom-based Social Studies (IPS) learning strategies in building the character of elementary school students. The background of this study is based on the importance of character education in IPS and the challenges of globalization that can erode local cultural values. To achieve this goal, this study uses a qualitative approach with a library research method, namely reviewing various literature related to local wisdom-based learning strategies in the context of IPS education. The results of the study indicate that the integration of local wisdom in IPS learning has a positive impact on improving academic understanding and character formation of students. Previous studies have revealed that the use of folklore, local traditions, and cultural practices in IPS learning can instill the values of mutual cooperation, honesty, and tolerance. In addition, an experience-based and community approach has been shown to increase student engagement and motivation to learn. However, this study also found several challenges in implementing this strategy, such as differences of opinion among educators, resistance from the community, and variations in students' academic results. Therefore, support is needed from various parties, including the government, schools, and the community, to overcome these challenges. Steps such as teacher training, development of local wisdom-based teaching materials, and socialization to the community need to be done so that this strategy can be implemented systematically and sustainably. Thus, local wisdom-based social studies learning can be a solution in forming a generation with strong character and high cultural awareness. Keywords : IPS, local wisdom, learning strategies, character education, elementary school.